Basophils in allergic immune responses. - Vöhringer, David (Current Opinion in Immunology, 2011)
Basophils are rare effector cells of the innate immune system. They are generally associated with type 2 immune responses that develop during helminth infections and allergic reactions. The role of basophils for initiation and execution of allergic immune responses is not well understood. Over the past few years new tools have been generated to study the function of basophils in mouse models. Depending on the experimental systems used conflicting results were obtained with regard to the role of basophils for initiation and execution of immune responses against allergens and helminths. This review highlights the current knowledge about basophil in vivo functions with a focus on the role of basophils for allergic responses like asthma, allergic skin diseases and anaphylaxis. © 2011 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2011.med.IKMI.pifto.basoph_9